2010
DOI: 10.4293/108680810x12924466007728
|View full text |Cite
|
Sign up to set email alerts
|

Port-Site Hernia Following Laparoscopic Cholecystectomy

Abstract: The incidence of port-site hernia is variable, but evidence suggests that awareness of risk factors and modification of technique can minimize risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 35 publications
(83 reference statements)
4
93
1
3
Order By: Relevance
“…The closed environment of the umbilicus region increases the risk of secretion and infection around the incision in patient groups operated with multi-channel devices. Bunting reports that hernia development is most common in the umbilicus among the trocar insertion sites (88.9%) [5,[22][23][24]. Although actual rates are not known, Alptekin et al found the frequency of port site hernia development after the SILC technique to be about 3.2 times higher than the LC technique [5].…”
Section: Post-operative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closed environment of the umbilicus region increases the risk of secretion and infection around the incision in patient groups operated with multi-channel devices. Bunting reports that hernia development is most common in the umbilicus among the trocar insertion sites (88.9%) [5,[22][23][24]. Although actual rates are not known, Alptekin et al found the frequency of port site hernia development after the SILC technique to be about 3.2 times higher than the LC technique [5].…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…It is interesting that hernias only developed with the SILC method although both the SILC and MCAP methods use an umbilical entry site. The operation duration and incision size have been reported to be important factors in hernia development after laparoscopic procedures [22,23]. The longer trauma duration to the umbilicus in the single port method can affect the blood circulation in the area.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…Bunting suggests that umbilical port alone should be used for retrieval of gallbladder during cholecystectomy and the defect closed under direct vision, and all ports of >10 mm should be closed especially when cutting trocars are used [10]. Some suggest closing of port site 5 mm or larger [6], and in children, even less than 5 mm ports are also suggested to be closed routinely [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cosmetic results of abdominal procedures could be further improved, inasmuch as it is a potentially scarless surgery. Minimizing incision-related complications could be even more important in the obese patient due to the negative effects of the thick abdominal wall causing greater postoperative pain and higher incisional hernia incidence rates [4]. The first report of a bariatric NOTES procedure in humans was published in 2008 by Ramos et al who presented their experience with trans-vaginal sleeve gastrectomy [5].…”
Section: Introductionmentioning
confidence: 99%